Clostridium difficile infection presenting as a leukemoid reaction: a case report and mini-review of the literature - Asif Dabeer Jafri; Muktesh Singh; Rehana Ansari; Ratender Kumar Singh (Emergency Care Journal, 2025)
Clostridium Difficile Infection (CDI) is a prevalent healthcare-associated infection primarily affecting the gastrointestinal tract. However, extraintestinal manifestations, such as abscess formation, are rare and pose significant diagnostic and therapeutic challenges. Furthermore, Clostridium difficile-associated Leukemoid Reactions (LR) are infrequent and often indicative of severe disease with poor prognostic implications. This report presents a rare case of an extraintestinal CDI manifesting as an abscess accompanied by a leukemoid reaction. A 50-year-old male presented with a fever and gait imbalance. Clinical examination revealed a febrile, hemodynamically unstable patient with an inflamed abscess in the right lumbar region. Laboratory investigations demonstrated marked leukocytosis and thrombocytosis. Despite initial empirical antimicrobial therapy with intravenous piperacillin-tazobactam and clindamycin, the patient exhibited persistent fever and progressive leukocytosis. Surgical drainage of the abscess was performed, and microbiological analysis identified Clostridium difficile. The antimicrobial regimen was modified to include intravenous metronidazole and vancomycin, resulting in clinical improvement and subsequent normalization of leukocyte counts. The patient made a complete recovery and was subsequently discharged. This case underscores the importance of considering atypical presentations of CDI, particularly in the absence of classical gastrointestinal symptoms. Early recognition, prompt surgical intervention, and targeted antimicrobial therapy are critical for favorable clinical outcomes. This report highlights the need for heightened clinical awareness regarding atypical presentations of CDI to ensure prompt diagnosis and optimal patient outcomes.